The Impact of the Strategy (Be - Share - Listen - Innovate) in Developing Conceptual and Procedural knowledge Among Female Primary School Students in Al-Qurayyat Governorate - Eida Munizel Harith Al-Ruwaili (Migration Letters, 2023)
The study aimed to reveal the effect of the strategy (Be - Share - Listen - Innovate) in developing conceptual and procedural knowledge among primary school students in Al-Qurayyat Governorate. To achieve the objectives of the study, the researcher prepared an achievement test in the unit of measurement (perimeter, area, and volume). It consists of (35) items distributed over (9) items in the field of mathematical concepts, (14) items in the field of mathematical generalizations, and (12) items in the field of skills and algorithms. The study sample amounted to (55) female students who were in the experimental group (30) female student, and the control group (25) female students from the Twelfth School for Girls, affiliated with the schools of the Al-Qurayyat Education Department, were randomly selected during the second semester of the year (2022-2023). The results of the study showed that the adjusted averages were in favor of the experimental group with higher adjusted arithmetic averages for mathematical concepts, mathematical generalizations, and procedural knowledge, meaning that the effect size value and practical significance for teaching using the strategy amounted to (0.519) for mathematical concepts, (0.605) for mathematical generalizations, and (0.553) for skills and algorithms, all of which are greater than the upper limit of the effect size according to the reference frame (0.14). The study recommended employing the strategy (Be - Share - Listen - Innovate) among mathematics teachers.